Transformasi TRANSFORMING LEARNING ORGANIZATION SYSTEMS FOR SUSTAINABLE INNOVATION IN ISLAMIC PRIVATE UNIVERSITIES - Hendrawati, Titi (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
The transformation of Islamic Private Higher Education Institutions (PHEIs) requires learning systems that go beyond structural reform by fostering a sustainable culture of collective learning and knowledge creation. Purpose: This study aims to analyze how the transformation of Learning Organization systems, integrated with the SECI knowledge creation model, enhances institutional performance and sustainable innovation in Islamic private universities. Method: A qualitative approach with a multiple case study design was employed at Universitas Pelita Bangsa and Universitas Islam 45 Bekasi. Data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed inductively using a phenomenological approach based on thematic cross-case analysis model. Data validity was ensured through triangulation and member checking. Results: The findings reveal that Learning Organization disciplines personal mastery, shared vision, team learning, mental models, and systems thinking have been partially implemented within academic and managerial practices. Their effectiveness is significantly strengthened when integrated with the SECI model, which operationalizes knowledge creation through socialization, externalization, combination, and internalization. This integration forms an integrative SECI–Learning Organization (SECI–LO) model that generates a continuous learning spiral supporting adaptability, innovation, and performance improvement. Conclusion: The study contributes theoretically by offering an integrative SECI–LO framework for Islamic higher education and provides practical guidance for institutionalizing learning and innovation through quality assurance systems, transformational leadership, and digital knowledge infrastructure.